Artes cênicas e a aprendizagem bilíngue: uma proposta para educandos dos sextos anos do ensino fundamental II - Fischer, Ismália Sales (2023)
This research fosters dialogic intersections between the realms of performing arts and English language learning. The study was conducted with two sixth-grade classes at the D. José Maria Pires Municipal Bilingual and Comprehensive School, situated in the Novais neighborhood of João Pessoa, Paraíba. The primary goal of this work focused on the development of interdisciplinary educational materials for the instruction of Theater/Dance and English. Within the scope of artistic exploration, theater games and movement investigation exercises were proposed to develop not just spoken language, but also body or gestural language, thereby fostering creativity and encouraging openness to experimentation and uninhibited expression. This curriculum seeks to gradually stimulate students to learn a second language by connecting the knowledge acquired in theater/dance to other disciplines. Consequently, this dissertation aims to contribute to the realization of a bilingual public school, strengthening the adoption of artistic knowledge not merely as a tool for foreign language learning, but also as a means of valuing artistic expression in alignment with teaching-learning practices and their specific content areas.